2002
DOI: 10.1074/jbc.m110598200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor α (PPARα) Turnover by the Ubiquitin-Proteasome System Controls the Ligand-induced Expression Level of Its Target Genes

Abstract: Peroxisome proliferator activated-receptor ␣ (PPAR␣) is a ligand-activated transcription factor belonging to the nuclear receptor family. PPAR␣ is implicated in the regulation of lipid and glucose metabolism and in the control of inflammatory response. Recently, it has been demonstrated that a number of nuclear receptors are degraded by the ubiquitin-proteasome pathway. Since PPAR␣ exhibits a circadian expression rhythm and since PPAR␣ is rapidly regulated under certain pathophysiological conditions such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 31 publications
5
85
0
3
Order By: Relevance
“…It has recently been demonstrated that inhibition of proteosomal degradation enhances the transcriptional response mediated by some nuclear receptors (Blanquart et al, 2002;Deroo et al, 2002;Pollenz, 2002) and the Ets protein E1AF (Takahashi et al, 2005). We show here that blocking protein turnover with the proteasome inhibitor ALLN or MG132 also induces a change in ERM transcriptional activity.…”
Section: Discussionsupporting
confidence: 53%
“…It has recently been demonstrated that inhibition of proteosomal degradation enhances the transcriptional response mediated by some nuclear receptors (Blanquart et al, 2002;Deroo et al, 2002;Pollenz, 2002) and the Ets protein E1AF (Takahashi et al, 2005). We show here that blocking protein turnover with the proteasome inhibitor ALLN or MG132 also induces a change in ERM transcriptional activity.…”
Section: Discussionsupporting
confidence: 53%
“…Several nuclear hormone receptors, such as RXR␣/␥, RAR␣, thyroid hormone receptor, and PPAR␥, are degraded by the ubiquitin-proteasome system (43)(44)(45). Recently, Blanquart et al (46) have shown that the protein stability of PPAR␣ is increased in the presence of its ligand WY 14,643 by decreasing its ubiquitination. Consistent with these reports, we show with a pulse-chase experiment that the stability of PPAR␥ increases in differentiated brown adipocyte cultures after treatment with norepinephrine in a manner similar to that caused by proteasome inhibitors.…”
Section: Fig 7 Nuclear Translocation Of Pka and Nf-bmentioning
confidence: 99%
“…5B). It has been shown that nuclear hormone receptors, including PPAR␣ and PPAR␥, are targets for the ubiquitin-proteasome system of protein degradation (43)(44)(45)(46). Because ligand activation has been shown to influence the stability of nuclear receptor proteins, the effect of norepinephrine on PPAR␥ was examined.…”
Section: Adipogenic Transcriptionmentioning
confidence: 99%
“…It may be reasonable to expect some mechanisms that rapidly sense and tightly control the activity of PPAR␣ according to metabolic needs under normal physiological condition. Degradation of PPAR␣ by the ubiquitin-proteasome system and decrease of the ubiquitination by the ligands of PPAR␣ may represent one of such mechanisms (Blanquart et al, 2002). Because feedback regulation, by which a transcription factor is negatively regulated by its target gene product, has been found for several nuclear receptors such as thyroid hormone receptor and retinoid receptor (Thompson and Bottcher, 1997;Kerley et al, 2001), a question may be raised as if any PPAR␣-target gene product can also negatively regulate PPAR␣ activity.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of PPAR␣ in physiology and disease is evidenced by the fact that it and PPAR␥, another subtype of PPARs, are molecular targets for the lipid-lowering fibrate drugs and insulin-sensitizing thiazolidinedione (TZD), respectively (Evans et al, 2004). Besides activation of PPAR␣ by fatty acid and various exogenous ligands such as fibrates, the regulation of the PPAR␣ transcription activity by coactivators (Dowell et al, 1997), corepressors (Dowell et al, 1999), other transcription factors (TFs; Zhou et al, 1999), and posttranslational modifications including phosphorylation (Juge-Aubry et al, 1999) and ubiquination (Blanquart et al, 2002) have been extensively studied. However, redox regulation of PPAR␣ activity has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%